1980
DOI: 10.1113/jphysiol.1980.sp013438
|View full text |Cite
|
Sign up to set email alerts
|

Functional capacities of tactile afferent fibres in neonatal kittens

Abstract: SUMMARY1. Responses were recorded from individual tactile afferent fibres isolated by microdissection from the median nerve of pentobarbitone-anaesthetized neonatal kittens (1-5 days post-natal age). Experiments were also conducted on adult cats to permit precise comparisons between neonatal and adult fibres.2. Neonatal fibres with receptive fields on the glabrous skin of the foot pads were classified into two broad groups, a slowly adapting class (40 %) which responded throughout a 1 see period of steady inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 35 publications
5
44
0
Order By: Relevance
“…First, units identified as central neurones had biphasic extracellular action potentials, 250-750 Its in duration (Connor et al 1984). They also had spontaneous activity and differed in their functional properties from those of primary fibres recorded in peripheral nerves (Ferrington & Rowe, 1980b;Connor et al 1984). Units identified as primary input fibres had brief, often monophasic action potentials, low or absent spontaneous activity, and a set of functional properties indistinguishable from those of peripherally recorded primary fibres (Ferrington & Rowe, 1982).…”
Section: Identification Of Dorsal Column Nuclei Neuronesmentioning
confidence: 99%
See 1 more Smart Citation
“…First, units identified as central neurones had biphasic extracellular action potentials, 250-750 Its in duration (Connor et al 1984). They also had spontaneous activity and differed in their functional properties from those of primary fibres recorded in peripheral nerves (Ferrington & Rowe, 1980b;Connor et al 1984). Units identified as primary input fibres had brief, often monophasic action potentials, low or absent spontaneous activity, and a set of functional properties indistinguishable from those of peripherally recorded primary fibres (Ferrington & Rowe, 1982).…”
Section: Identification Of Dorsal Column Nuclei Neuronesmentioning
confidence: 99%
“…1 and 2) whereas individual P.c. fibres often reach a response plateau at 5-10 /tm (Talbot et al 1968;Ferrington & Rowe, 1980b).…”
Section: Neurones To Cutaneous Vibrationmentioning
confidence: 99%
“…fibres up to 800-1000 Hz (Hunt, 1961;Talbot et al 1968;Ferrington & Rowe, 1980b;Ferrington, Hora & Rowe, 1984), the behaviour of the dorsal column nuclei neurones nevertheless parallels the steep decline observed in the subjective capacity for vibration frequency discrimination (von Bekesy, 1962;Goff, 1967;Rothenberg, Verrillo, Zahorian, Brachman & Bolanowski, 1977). The Weber fraction, Af/f, for frequency discrimination increases steeply above 100-200 Hz, its value being about 03-0{4 at 200 Hz (Goff, 1967;Rothenberg et al 1977) whereas in the range 350-450 Hz, von Bekesy (1962) reported that doubling the vibration frequency no longer raised the pitch, a finding that implies a Weber fraction > 1.…”
Section: Integrative Processing In Dorsal Column Nucleimentioning
confidence: 99%
“…receptors and their associated P.c. sensory fibres (Janig, Schmidt & Zimmermann, 1968;Talbot, Darian-Smith, Kornhuber & Mountcastle, 1968;Iggo & Ogawa, 1977;Ferrington & Rowe, 1980b). Over their whole frequency range, the P.c.…”
Section: Introductionmentioning
confidence: 99%